Nigeria : Publication of Financial Sector Assessment Program Documentation -- Detailed Assessment of Implementation of IOSCO Objectives and Principles of Securities Regulation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
An assessment of the level of implementation of the International Organization of Securities Commissions (IOSCO) Principles in Nigeria was conducted as part of the International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP). The ongoing global financial crisis has reinforced the need for assessors to make a judgment about supervisory practices and to determine whether they are sufficiently effective. The assessment methodology provides a set of assessment criteria to be met in respect of each principle to achieve the designated benchmarks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet